Relationship Parental Attention And Learning Achievement In High School Students - Farisa Suhadi; Khairani Khairani (Jurnal Neo Konseling, 2019)
Parents attention gives a big role in students' learning success. But in reality there are still many students who have not received the attention of parents. This study aims to describe (1) parental attention, (2) student achievement, and (3) examine the relationship of parental concern with student achievement. This research uses descriptive correlational method. The study population was 432 students in grade XI and XII of SMA Pertiwi 1 Padang and a sample of 208 students used stratified random sampling technique. The instrument used was a questionnaire parental attention and learning achievement seen from the semester 2 grades of the 2018/2019 school year. Data were analyzed using descriptive statistics and Pearson Product Moment techniques to determine the relationship of parental attention to student achievement through the statistical program SPSS for windows release 20.0. The results showed that (1) parental attention was in the medium category, (2) student achievement was in the high category, (3) there was a significant positive relationship between parental attention and student learning achievement with a coefficient of 0.137 with a significant value of sig. ( 2-tailed) of 0.048 and Pearson Correlation value of 1 with a weak relationship level.